Studi Kasus : Pengetahuan dan Persepsi Masyarakat Tentang Vaksin Covid-19 - Teti Sutriati Tuloli; Nur Rasdianah; Nur Ain Thomas; Madania Madania; Devie Ariany Daud (State University of Gorontalo, 2022)
The Covid-19 vaccine is still often rejected by the public, especially those who are in places with a lack of information. This affects the public knowledge and perception of the Covid-19 Vaccine. The objective of this study is to determine the level of public knowledge and perception about the Covid-19 Vaccine and to determine the correlation between the characteristics of public and perception of the Covid-19 vaccine and the correlation between the level of public knowledge and perception about the Covid-19 Vaccine. This research is observational research with a quantitative descriptive research design using a cross-sectional approach. The findings indicate that the knowledge level of the people in Tuladenggi Village about the Covid-19 Vaccine in the low category is 22%, medium category is 46%, and high category is 33%. On the other hand, the perception of people in Tuladenggi Village about Covid-19 Vaccine in the negative category is 21%, the neutral category is 25%, and the positive category is 55%. Some of the respondents' characteristics, namely Age, Occupation, Education, Marital Status, Disease History, Vaccination Status, Vaccine Type, and Symptoms, have a significant correlation with perception, with a p-value lower than 0.005. In contrast, Gender and Religion do not have a significant correlation with perception, with a value, higher than 0.005. The correlation between the level of public knowledge about vaccine and perception obtains p-value of 0.000 (p0.05).